Mucoepidermoid carcinoma of the breast: A case report and literature review focused on radiological findings. Issue 26 (30th June 2022) - Bak, Seongjun; Choi, Hye Young; Lee, Jeong-Hee; Na, Jae Beom; Choi, Dae Seob; Cho, Jae Min; Choi, Ho Cheol; Park, Mi Jung; Kim, Ji Eun; Shin, Hwa Seon; Won, Jung Ho; Kim, Ju-Yeon; et al.
Abstract : Rationale: Mucoepidermoid carcinoma (MEC) of the breast is a rare entity, with an estimated incidence of only 0.2% to 0.3% of all primary breast tumors. The radiological features of breast MEC have scarcely been investigated mainly because of its rarity. In this article, we present a case of breast MEC diagnosed at our hospital and review the literature, focusing on radiological findings and radiologic–pathologic correlations that could improve clinical management of this entity. To the best of our knowledge, our study is the first review of the literature that focuses on the radiological features of breast MEC. Patient concerns: A 47-year-old premenopausal woman presented with a painless palpable mass in the right breast. Diagnosis: Mammography and ultrasonography revealed a mass with suspicious malignant features, which was categorized as Breast Imaging Reporting and Data System category 4c. A 14-gauge core-needle biopsy revealed an intermediate-grade MEC of the breast. The patient underwent breast magnetic resonance imaging and chest computed tomography for preoperative evaluation. Postoperative histopathological examination confirmed a diagnosis of intermediate-grade MEC. The clinical staging was T2N0M0. Interventions: The patient underwent breast-conserving surgery, adjuvant chemotherapy, radiotherapy, and hormonal therapy. Outcomes: No evidence of recurrence has been reported over 37 months. Lessons: The imaging characteristics of breast MEC were variable, and there were no specific radiological features for diagnosis. The presence of cystic components on radiological imaging is likely to be an indicator of a low-grade tumor and better prognosis, although the number of reported cases is limited.